2019
DOI: 10.1186/s12889-019-7546-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between alcohol, marijuana, illegal drug use and current use of E-cigarette among youth and young adults in Canada: results from Canadian Tobacco, Alcohol and Drugs Survey 2017

Abstract: Background: E-cigarettes have grown in popularity around the world since 2003. Although marketed as a smoking cessation tool, e-cigarettes can lead to tobacco cigarette smoking in youth. In Canada, among all age groups, youth and young adults have the highest prevalence of e-cigarette use. The objective of this study was to assess the factors associated with e-cigarette use among youth and young adults in Canada, and to specifically examine the association between alcohol, marijuana and illicit drug use. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 44 publications
3
26
3
1
Order By: Relevance
“…Future research could take into account e-cigarettes that do not contain nicotine and e-cigarettes that contain other addictive substances, since e-cigarettes can also be used as illicit drug delivery systems [45]. Future studies could also attempt to determine the frequency of use among current users of e-cigarettes and study potential misconceptions about the safety of e-cigarettes among the general public and adolescents in particular [46,47].…”
Section: Further Research Directionsmentioning
confidence: 99%
“…Future research could take into account e-cigarettes that do not contain nicotine and e-cigarettes that contain other addictive substances, since e-cigarettes can also be used as illicit drug delivery systems [45]. Future studies could also attempt to determine the frequency of use among current users of e-cigarettes and study potential misconceptions about the safety of e-cigarettes among the general public and adolescents in particular [46,47].…”
Section: Further Research Directionsmentioning
confidence: 99%
“…EC users have an increased risk of alcohol misuse (Figure 1), such as binge drinking or chronic use, when compared with non-EC users (Lanza and Teeter, 2018;Mehra et al, 2019). While the literature is replete for this trend with the use of traditional cigarettes and alcohol consumption, a similar public health issue may exist for EC use and requires future study.…”
Section: Trend Of Ec and Alcohol Dual Usementioning
confidence: 99%
“…Statewide data from 2016 also show similar higher prevalence of household, peer and individual factors associated with youth substance use among grade 10 marijuana users than nonusers (https://www.askhys.net/library/2016/RecentMarijaunaUseGr10.pdf). Findings from a 2017 survey of Canadian residents aged 15–24 years found that marijuana users were significantly more likely to be past 30-day e-cigarette users, compared with nonusers ( 8 ). Polysubstance use and driving after using marijuana or riding in a car driven by someone who had used marijuana recently are public health issues that are important to monitor.…”
Section: Discussionmentioning
confidence: 99%